2016
DOI: 10.1186/s12885-016-2898-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone is increased in the lungs and enhances experimental lung metastasis of melanoma in DJ-1 KO mice

Abstract: BackgroundGrowth hormone (GH) mainly serves an endocrine function to regulate somatic growth, but also serves an autocrine function in lung growth and pulmonary function. Several recent studies have demonstrated the role of autocrine GH in tumor progression in some organs. However, it is not clear whether excessive secretion of GH in the lungs is related to pulmonary nodule formation.MethodsFirstly, the lung tissues dissected from mice were used for Western blotting and PCR measurement. Secondly, the cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…GH-treated cells demonstrate increased capacity for anchorage-independent growth, consistent with our in vivo results showing increased metastatic potential of colon cells in the presence of high-circulating GH. Others have shown that high GH increased murine pulmonary melanoma metastases (78). These prometastatic effects may be attributed to both GH-mediated DDR suppression and EMT activation (24).…”
Section: Discussionmentioning
confidence: 96%
“…GH-treated cells demonstrate increased capacity for anchorage-independent growth, consistent with our in vivo results showing increased metastatic potential of colon cells in the presence of high-circulating GH. Others have shown that high GH increased murine pulmonary melanoma metastases (78). These prometastatic effects may be attributed to both GH-mediated DDR suppression and EMT activation (24).…”
Section: Discussionmentioning
confidence: 96%
“…Further, we and others have shown a direct effect of GH–GHR action in upregulating expression of ATP-cassette-containing (ABC) multidrug efflux pumps such as ABCB1, ABCC1, ABCC2, and ABCG2 in melanoma [21] as well as in breast cancer [22]. Increased GH production in other tissues, such as lungs, has been found to guide lung metastasis of B16F10 melanoma xenografts in DJ1-KO mice [23]. Therefore, it appears that the GH–GHR pair is harnessed to particularly evade therapeutic challenges by advanced melanoma tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we had reported that not only do melanoma cells overexpress GHR but also that targeting GHR in human melanoma cells attenuates tumor progression, EMT induction, drug efflux and more importantly, sensitizes these cells to chemotherapy in vitro [57,58]. Additionally, enhanced metastasis of mouse melanoma cells to the lungs in response to locally elevated GH levels in DJ-1 knockout mice was recently reported and confirms a role of GHR in melanoma metastases [4]. Our current study provides a first in vivo validation to our earlier in vitro mechanistic observations on the role of GH in melanoma chemoresistance.…”
Section: Discussionmentioning
confidence: 56%
“…Accumulating evidence implicates growth hormone (GH) in the development and progression of a wide range of malignancies [1][2][3][4][5][6][7], including breast [8][9][10][11][12][13][14][15], prostate [16,17], colorectal [18,19], glioma [20], pancreatic [21], thyroid [22], liver [23] and endometrial cancers [24,25]. GH is a peptide hormone produced by pituitary somatotrophs and acts on multiple tissues including bone, muscle, fat, liver, pancreas, heart, thymus and kidney.…”
Section: Introductionmentioning
confidence: 99%